2018
DOI: 10.1002/ijgo.12648
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of continuous Doppler versus intermittent fetoscope fetal heart rate monitoring in a low‐resource setting

Abstract: Continuous FHR monitoring increased identification of abnormal FHR and subsequent intrauterine resuscitations. ClinicalTrials.gov: NCT02790814.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 16 publications
3
57
0
Order By: Relevance
“…Although this approach underreports the problem, the findings highlight the challenge of adhering to guidelines in these settings. In other resource-limited settings of Sub-Saharan Africa, randomised control trials on innovative FHRM devices failed to show improvement in perinatal outcomes due Values are given as mean (standard deviation) *Significant level at 0.05: there were less senior doctors in the evening and night, and less intern doctors at night compared to morning shifts to non-adherence to FHRM international guidelines and obstetric response [21][22][23][24]. In this hospital, international guidelines were adapted to locally-acceptable minimum standards [9].…”
Section: Discussionmentioning
confidence: 99%
“…Although this approach underreports the problem, the findings highlight the challenge of adhering to guidelines in these settings. In other resource-limited settings of Sub-Saharan Africa, randomised control trials on innovative FHRM devices failed to show improvement in perinatal outcomes due Values are given as mean (standard deviation) *Significant level at 0.05: there were less senior doctors in the evening and night, and less intern doctors at night compared to morning shifts to non-adherence to FHRM international guidelines and obstetric response [21][22][23][24]. In this hospital, international guidelines were adapted to locally-acceptable minimum standards [9].…”
Section: Discussionmentioning
confidence: 99%
“…In another RCT in Tanzania, an increase in risk of intrauterine resuscitation was observed for women continuously monitored with Doppler as compared with those intermittently monitored with Pinard (RR, 2.07; 95% CI, 1.4-2.9); as described above, there was no difference in adverse perinatal outcomes between the two arms. 20 In Tanzania, two RCTs of intermittent monitoring with Doppler versus intermittent monitoring with Pinard did not find a difference in time from abnormal FHR detection to delivery between the two arms. 17,18 In Zimbabwe, there was no difference in mean duration of labor among the four study groups.…”
Section: Findings On Clinical Management Associated With Abnormal Fhrmentioning
confidence: 94%
“…Six studies addressed the effectiveness of Doppler versus Pinard stethoscope for the detection of abnormal FHR during intermittent or continuous FHR monitoring in the intrapartum period (Table 1). [15][16][17][18][19][20] Freeplay (wind-up) Doppler, 17 Moyo strap-on Doppler using the continuous or intermittent monitoring function, 18,19 and the Huntleigh pocket Doppler. 15…”
Section: Fhr Abnormalities and Adverse Perinatal Outcomesmentioning
confidence: 99%
“…As part of the Safer Births project, a randomized controlled study, carried out in rural settings in Tanzania, revealed that the use of Moyo increased the identification of baseline abnormal FHR and subsequent intrauterine resuscitations. 66 Further, qualitative studies on the preferences and acceptability of the strap-on Moyo device among mothers and clinical staff have been conducted. The findings of these studies show that preference and acceptance was high compared to other devices.…”
Section: Safer Births Project and The Development Of An Automatic Strmentioning
confidence: 99%
“…69 The second study compared the Moyo with the Pinard method and showed that the use of Moyo increased FHR detection and intrapartum resuscitations compared to the Pinard with similar perinatal outcomes. 66…”
Section: Current Fhr Monitoring Practicesmentioning
confidence: 99%